2017
DOI: 10.18203/2320-1770.ijrcog20175546
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of carcinoma cervix in nursing personnel of a tertiary care institute, Mumbai, India

Abstract: Background: Carcinoma cervix is the second most common cancer of women all over the world and commonest cancer among Indian women. Awareness about cervical cancer and its prevention low amongst Indian women. The Pap test is a simple cost-effective technique for screening to help early diagnosis of cervical cancer. Nursing staff should be made aware of cervical cancer, so that they can spread the knowledge to the general public. Objectives of present study were to assess the knowledge level regarding symptoms, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…In the present study, 83.3% of people knew that PAP smear test detects cervical cancer even before the symptoms appear, which were in comparison with similar studies [13][14][15]. While 29.2%% of the eligible participants have undergone PAP smear test in our study, it was only 5% in few other studies [16,17]. This shows that we lack an organized opportunistic screening program for cervical cancer in India.…”
Section: Discussionsupporting
confidence: 45%
“…In the present study, 83.3% of people knew that PAP smear test detects cervical cancer even before the symptoms appear, which were in comparison with similar studies [13][14][15]. While 29.2%% of the eligible participants have undergone PAP smear test in our study, it was only 5% in few other studies [16,17]. This shows that we lack an organized opportunistic screening program for cervical cancer in India.…”
Section: Discussionsupporting
confidence: 45%
“…[11][12][13] But only 29.2% had PAP test in our study but it was only 5% in few studies 14,15. This shows that we lack an organized opportunistic screening program for cervical cancer in India.…”
mentioning
confidence: 71%
“…Notably, the study found superior knowledge among tertiary-level nursing staff in comparison to previous studies, with a higher proportion correctly identifying risk factors and demonstrating improved awareness of HPV. [ 3 4 ] Despite this enhanced knowledge, the translation into improved practices was not straightforward. Only about 3% of tertiary care nursing staff underwent self-pap smear testing, indicating a gap between awareness and pro-active practices.…”
Section: R Esults and Discussionmentioning
confidence: 99%